SOCIAL CAPITAL AMONG URBAN AGRICULTURE PROGRAM PARTICIPANTS IN KLANG PERDANA SELANGOR, MALAYSIA - Nur Shuhamin Nazuri; Nobaya Ahmad (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The aim of the study is to measure the level of social capital among urban agriculture program participants in Klang Perdana, Selangor. The study employed quantitative research using a survey method. A total of 30 respondents were involved to answer the questionnaire in the preliminary study. The findings were based on the pilot test prior to the commencement of the actual data collection. The result indicated that the community in Klang Perdana who participated in the urban agriculture program have a high level of social. Analysis using t-test and ANOVA revealed that age and gender variables have a significant effect on their social capital. Social capital was found to be important in increasing the participation of the community in urban agriculture programs.